The Opportunities and Challenges of Student Paralegal within University Legal Clinic at PTKIN - Yusup, Deni K; Hamnach, Burhanuddin; Sumner, Cate (Universitas Islam Negeri Raden Intan Lampung, 2019)
This paper is motivated by the role of the university legal clinic under the spirit of implementing the third of university role in the field of community service. In practice, legal aid services at universities are not different from general aid agencies in general. One of the uniqueness of the university legal clinic program is the direct involvement of student paralegal in helping the clients to get legal aid services within the university and court. The student paralegal encounters various opportunities and challenges. The main opportunities, they have their passion and strong motivation to become justice fighters for justice seekers, while they have also the main challenges such as limited time, facilities, knowledge, and legal skills. However, the existence of student paralegal has proven to be very helpful for the clients not only in processing applications and registering cases in court but also in assisting clients in the form of consultation and legal assistance during non-litigation and litigation. Therefore, the university legal clinic program needs to be further strengthened and developed at PTKIN because it has proven positive implications for helping underprivileged people and justice seekers to get access to justice.